2011
DOI: 10.32637/orli.v41i1.57
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan obstructive sleep apnea dengan penyakit sistem kardiovaskuler

Abstract: Background: Obstructive sleep apnea (OSA) is a disease characterized by periodic upper airway collapse during sleep, which could result in either apnea, hypopnea or both. OSA is very often  undetected but it is strongly associated with variety of medical complication, among others cardiovascular diseases.Purpose: To inform ENT specialists about the pathogenesis and pathophysiology of OSA and its complications. Literature review: Recent data from several studies has documented the association between OSA and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…[15][16][17] Obesity can alter the volume and shape of the anatomy of the tongue so that the tongue raises that will ultimately reduce the volume of the upper respiratory tract. 13 Based on the results of the study revealed that the likelihood of obesity could worsen OSA because of fat deposits on the specific location. The buildup of fat in the tissue around the airway the top producing lumen airway smaller and improvement of collapsibility of the upper respiratory tract, so that contribute to the onset of apnea.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…[15][16][17] Obesity can alter the volume and shape of the anatomy of the tongue so that the tongue raises that will ultimately reduce the volume of the upper respiratory tract. 13 Based on the results of the study revealed that the likelihood of obesity could worsen OSA because of fat deposits on the specific location. The buildup of fat in the tissue around the airway the top producing lumen airway smaller and improvement of collapsibility of the upper respiratory tract, so that contribute to the onset of apnea.…”
Section: Discussionmentioning
confidence: 93%
“…OSA is the state of occurrence of upper airway obstruction periodically during sleep that causes intermittent breath stop, either complete (apnea) or partial (hypopnea). 13 Obesity is a risk factor for going to his various diseases in developing countries and the developing countries, for example, the disease due to obesity, such as type II DM, hypertension, cardiovascular disease, obstruction sleep apnea/ hypopnea syndrome (OSAHS). 14 A variety of methods can be used to find out the Anthropometry happened his obesity; these methods include measurement of BMI, waist circumference, hip circumference, arm circumference, and circumference of the neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OSA merupakan sindrom pernapasan gangguan tidur dimana episode abnormal frekuensi pernapasan dikaitkan dengan penyempitan periodik saluran udara bagian atas selama tidur, yang mengakibatkan henti napas intermiten, baik penurunan ventilasi sebagian (hypopnea) atau penghentian pernapasan total (apnea). 4 Faktor risiko yang dapat meningkatkan risiko terjadinya OSA seperti usia, lingkar leher, aktivitas fisik, kebiasaan merokok, jenis kelamin, dan obesitas. Obesitas menjadi salah satu risiko utama lansia mengalami OSA.…”
Section: Pendahuluanunclassified